Espiritualidade e currículo: a voz dos professores de uma escola confessional do estado do Piauí - Oliveira, Maria das Graças Ferreira de (2012)
The aim of this PhD Thesis, entitled Spirituality and Curriculum: the teachers voice of a confessional school in Piaui State, resulting from a research conducted at a school of basic education, was to examine the extent to which the spirituality of a confessional school is revealed in the teachers voices and is present in curriculum. The discussed thematic is part of a school context that acknowledges the Christian religion and which is maintained by a Women's Religious Congregation. We emphasize three aspects developed in this study: the revelation of spirituality in teachers voice, their interaction with spirituality at school, and the prevalence of spirituality in the curriculum. The theoretical foundation of this thesis is on the works of Morin, Boff, Sacristán, Pacheco, Abramowicz, among others. A qualitative research data collection was carried out through document analysis procedures and application of two questionnaires. They reflect the urgency of a route of spiritual formation for the teacher in order that the teaching and learning process reaches the ideal of an education directed towards an education in values and for values, an education whose objective centers on the integral formation process of human beings. In this context, the relevance of this research is related to the possibility of providing an education which allows enough space to attitudes and behaviors of welcoming, respect, availability, generosity, solidarity with each other, knowing that we are responsible for each other as well as that spirituality provides grounds to both the pedagogical practice and the curriculum of confessional schools